ACADEMIC RESILIENCE IN LEARNING: LITERATURE REVIEW - Nurjamal; Siti Irene Astuti Dwiningrum; Mat Wajib (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2026)
Academic resilience is a multifaceted construct that enables students to adapt, persist, and thrive academically despite facing various challenges and adversities. It involves not only overcoming obstacles and bouncing back from academic setbacks but also maintaining a positive engagement with learning. This study reviews the findings of previous research. The review encompasses the concept, influencing factors, and strategies for strengthening academic resilience. The method employed is a literature review, examining national and international scholarly articles published between 2015 and 2025. Analysis was conducted through thematic identification. Variables were categorized, and relevant empirical findings were synthesized. The results indicate that academic resilience is influenced by internal factors, including self-efficacy, emotional regulation, and intrinsic motivation. External factors also play a role, such as social support, school climate, and the teacher's role. Strategies for strengthening academic resilience include a growth mindset-based learning approach and socio-emotional interventions. Educational policy support focused on students' psychological well-being is also crucial. In conclusion, academic resilience is a multifaceted construct influenced by the complex interplay of personal and environmental factors. Strengthening strategies focusing on a growth mindset, socio-emotional interventions, and educational policies oriented towards students' psychological well-being are essential in building learning resilience.